Plan estratégico de Marketing para la Corporación Grameen de la ciudad de Loja, periodo 2022-2024. - Gutiérrez Enríquez, Ericka Chelsea (2023)
The objective of this degree work is to prepare a "Strategic Marketing Plan for the Grameen corporation of the city of Loja, period 2022 - 2024", which allows the development of strategies based on a situational analysis of the company, both internal and external. external; internally, where through the EFI matrix a weighted value of 2.55 was obtained, which means that the corporation has more strengths and fewer weaknesses; externally, the EFE matrix released a weighted value of 2.80, which represents that the corporation is taking advantage of the opportunities and minimizing the threats, through the competitive profile matrix a value of 2.70 was obtained, which means that the corporation does have competition within the market in which it develops, in this case its competition The strongest are the cooperative Minga and Banco Finca, the approach that was applied in this research was the quantitative and qualitative approach (mixed exploratory-conclusive research), through deductive reasoning, the type of study that was implemented was descriptive-interpretative. , here an ordering of the results of the observations of given phenomena and situations was carried out, in this investigation the current situation, both internal and external, was determined. External omo of the corporation based on its 4ps (price, product, place and promotion), which allowed the realization of the Marketing Plan with the development of strategic objectives, giving a total cost of $1,450.90. Finally, the main conclusions are mentioned, among the most important are, that through the investigation of the needs and expectations of the clients, it was possible to determine strategies to increase the number of partners, retain the clients that the Grameen corporation currently has and generate higher market value.